Design and structure of nitrogen and oxygen co-doped carbon spheres with wrinkled nanocages as active material for supercapacitor application. (December 2021) - Liu, Zhisen; Qin, Aimiao; Zhang, Kaiyou; Lian, Peng; Yin, Xudong; Tan, Hua
Abstract: Nitrogen/oxygen co-doped carbon spheres with wrinkled nanocages (NOCN) were successfully synthesized using dendritic fibrous nanosilica (DFNS) as sacrificial solid template, glucose as a carbon source, and melamine as the nitrogen source. The obtained carbon nanocages (NOCN-850-3) exhibit human brain-like winkle shape, high specific surface area (813 m 2 g −1 ), high nitrogen (16.24 at%) and oxygen contents (5.36 at%). In addition, the obtained carbon presents good specific capacitance of 311.1 F g −1 at a current density of 0.5 A g −1 in 6 M KOH and remarkable rate performance (118.1 F g −1 at a current density of 30 A g −1 ) and cycle stability (97.6% retention after 10, 000 charge–discharge performance cycles at 10 A g −1 ). Meanwhile, the NOCN-850-3-based coin-type symmetric supercapacitor exhibits a maximum energy density of 12. 3 W h kg −1 at a power density of 175 W kg −1 and also a relatively low resistance in 6 M KOH aqueous electrolyte. Thus, the unique structure and nitrogen/oxygen co-doping characteristic endue the electrode material a potential application in supercapacitors. Graphical Abstract: ga1 Highlights: A facile strategy for the fabrication nitrogen/oxygen co-doped carbon spheres with wrinkled nanocages is proposed. The optimal carbon (NOCN-850-3) possesses a high specific surface area, high nitrogen and oxygen contents. NOCN-850-3 exhibits superior supercapacitive behavior to many previous carbon materials.